Comparative Typological Analysis of Poetics of Uzbek and English Fairy Tales (Zien Journal of Social Sciences and Humanities, 2022)
In this article, the general characteristics, structure, character of folk tales in English and Uzbek folklore are discussed and analyzed. Features of folk tales that differ from other types of folklore, level of study in English and Uzbek languages.